Peningkatan Kapasitas Pengelolaan Keuangan dan Pemasaran Digital Pada BUMDes Sumberdem Gemilang - Salsa Rahmawati Saputri; Trivena Gilang Permatasari; Agung Winarno; Wening Patmi Rahayu (Fakultas Teknik, Universitas PGRI Banyuwangi, 2026)
This community service initiative aims to enhance the capacity of BUMDes Sumberdem Gemilang in digital marketing and financial management. The main challenges faced by the partner include the suboptimal use of social media for product promotion and the lack of a structured financial record-keeping system. The program was implemented over three months, involving two managers and benefiting 8 BUMDes members through four phases: orientation, identification, implementation, and evaluation. The implementation phase included training and mentoring on social media management, digital content creation, and Excel-based financial record-keeping. Evaluation was conducted through observation and a comparison of the partner’s performance before and after the program. The results showed an improvement in social media performance, reflected in the number of followers, interactions, and content views. However, the implementation of the financial record-keeping template was not yet fully optimized due to human resource constraints and participants’ lack of understanding regarding digital financial administration. Therefore, ongoing support and further training are needed to strengthen the sustainability of financial management practices and expand the marketing reach of BUMDes products.